Longitudinal proteomic profiling reveals increased early inflammation and sustained apoptosis proteins in severe COVID-19 - Haljasmägi, Liis; Salumets, Ahto; Rumm, Anna Pauliina; Jürgenson, Meeri; Krassohhina, Ekaterina; Remm, Anu; Sein, Hanna; Kareinen, Lauri; Vapalahti, Olli; Sironen, Tarja; Peterson, Hedi; Milani, Lili; et al. (Scientific reports, 2020)
SARS-CoV-2 infection has a risk to develop into life-threatening COVID-19 disease. Whereas age, hypertension, and chronic inflammatory conditions are risk factors, underlying host factors and markers for disease severity, e.g. requiring intensive care unit (ICU) treatment, remain poorly defined. To this end, we longitudinally profiled blood inflammation markers, antibodies, and 101 plasma proteins of hospitalized COVID-19 patients who did or did not require ICU admission. While essentially all patients displayed SARS-CoV-2-specific antibodies and virus-neutralization capacity within 12–15 days, a rapid, mostly transient upregulation of selective inflammatory markers including IL-6, CXCL10, CXCL11, IFNγ, IL-10, and monocyte-attracting CCL2, CCL7 and CCL8, was particularly evident in ICU patients. In addition, there was consistent and sustained upregulation of apoptosis-associated proteins CASP8, TNFSF14, HGF, and TGFB1, with HGF discriminating between ICU and non-ICU cohorts. Thus, COVID-19 is associated with a selective inflammatory milieu within which the apoptotic pathway is a cardinal feature with potential to aid risk-based patient stratification.